Ritual Pluralism and Value Pluralism: On why one ritual is never enough - Joel Robbins (Suomen Antropologi, 2017)
It appears that every religious tradition contains within its repertoire of enjoined or encouraged actions more than one ritual. This article pursues the question of why this should be so. It develops an answer by making two basic claims. The first is that all societies are marked by the presence of more than one value. The second is that one thing rituals do is allow people to realize one value at a time in fairly full form—something people rarely accomplish in daily life, but that is important for them if they are to come to understand and develop a genuine attraction to these values. If both of these claims hold, then one reason religions need to offer more than one ritual is that people hold more than one value and they need separate rituals to be able to learn about and to experience what it is like to realize each of them in full form. The article concludes with a brief reflection of the importance of its analysis of value and ritual for the study of situations of religious pluralism.